The Frequent Application of Multicomponent and Cycloaddition Reactions for the Synthesis of Potent MDM2-p53 Inhibitors - Gollner, Andreas (Synlett, 2015)
Multicomponent reactions (MCRs) and cycloaddition reactions can generate structurally complex molecules in a very efficient manner and are a valuable tool not only for the synthesis of compound libraries for screening campaigns, but also for the optimization of compounds during lead optimization. This article highlights the frequent application of these reactions for the synthesis of potent inhibitors of the MDM2-p53 protein–protein interaction.
Keywords: multicomponent reaction; cycloaddition; antitumor agents; drugs; medicinal chemistry